Informar, conmover, culpar : retórica para reyes en la Brevísima relación del padre Las Casas - Martínez Torrejón, José Miguel (El Colegio de México, 2009)
This article explores the conflict between the rhetorical and historical nature of the Brevísima relación, taking into account the differences found between the three textual layers (1542, 1546, 1552) that constitute the version we now know as one homogeneous text. There are profound differences among the layers as they respond to different political needs. Most notably, the role of the Crown grows from simple destinatary of a historical report to become the object of a warning, more threatening because it is made in print, before an ample public: if the rulers continue to ignore their prescribed role as good shepperds, they will be considered tyrants.